(untitled) (Journal of Hama University, 2026)
The Study Aimed to Identify the impact of government spending on the gross domestic product in Syria during the period from 2013 to 2022, the descriptive approach was used and appropriate statistical methods ware relied upon to achieve the study objective and to analyze and interpret the data to reach conclusions and proposals. To test the hypothesis, the statistical program spss was relied upon. The study reached the following results: 1.There is a correlation between government expenditure and GDP, with a correlation coefficient of 98%, which is a strong correlation, and government expenditure explains 97% of the changes in GDP. 2.There is a direct relationship between government expenditure and GDP, which is consistent with economic literature. 3.There is a statistical impact of government expenditure on the GDP in Syria during the period from 2013 to 2022.